Health Monitoring System with Hybrid Laser Sensor Networks and Cloud Computing for Subway Tunnels - Fu-guang Zhu; Dong-sheng Xu; Rui-shan Tan; Bin Peng; He Huang; Zhuo-wen Liu (Advances in Civil Engineering)
The settlement and deformation monitoring for existing tunnels would encounter the difficulties in sensor installation and health evaluation in real time. Thus, it is necessary to develop effective methods for settlement and deformation measurements in the existing tunnels. This study proposed a more practical tunnel deformation monitoring theory and developed remote wireless tunnel deformation real-time monitoring and early warning system based on infrared laser ranging technology and cable sensing technology. The system could monitor the settlement and deformation of the tunnel in real time from a long distance and transmit the deformation data wirelessly in real time; then, three-dimensional space model of tunnel deformation was established, which intuitively and comprehensively reflected the actual deformation of the tunnel and intelligently identified the deformation. Finally, based on the practice of deformation control during tunnel excavation at Xiaohongshu Station of Wuhan Metro Line 8 of China, the measurement results of this new method were compared with the measurement results of particle image velocimetry technology (PIV), the reliability of the new tunnel deformation monitoring method was proved, the settlement error of each monitoring point was found to be less than 1 mm, and the deformation trend was consistent with the actual deformation. The results of this research could provide useful guidance for tunnel deformation monitoring.